Dominance of unicellular cyanobacteria in the diazotrophic community in the Atlantic Ocean. (24th March 2014) - Agawin, Nona S. R.; Benavides, Mar; Busquets, Antonio; Ferriol, Pere; Stal, Lucas J.; Arístegui, Javier
Abstract : The horizontal and vertical distribution of representatives of diazotrophic unicellular cyanobacteria was investigated in the subtropical northeast Atlantic Ocean (28.87 to 42.00°N; 9.01 to 20.02°W). Samples from stations encompassing different water conditions (from oceanic oligotrophic waters to upwelling areas and a temperature range of 13.1°C to 24.2°C) were size fractionated and analyzed for nifH by a nested polymerase chain reaction (PCR) and by tyramide signal amplification—fluorescence in situ hybridization (TSA‐FISH) using probe Nitro821. In samples from the surface, mixed‐layer depth, and deep chlorophyll maximum waters, most (> 50%) of the nifH recovered was from the 0.2–3 µm fraction and was consistent with TSA‐FISH counts. The < 3 µm Nitro821‐positive cells were more abundant than the larger cells, and the proportion of single cells was larger than that associated with particulate matter or with larger cells. Phylogenetic analysis of representative samples revealed that most of the sequences belong to diazotrophic unicellular cyanobacteria Group A (UCYN‐A or Candidatus Atelocyanobacterium thalassa). N2 fixation in the 0.2–3 µm fraction, putatively representing the activity of UCYN‐A, contributed more than 50% of the total N2 fixation. There was a positive relationship of this putative UCYN‐A abundance and activity with temperature, and a negative relationship with dissolved O2 . The dominance of these putative UCYN‐A organisms in nitrate‐rich upwelling filament regions suggests that the activity of this group of organisms may not be strongly controlled by the availability of fixed N.